2013
DOI: 10.1002/bmc.2867
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of nalbuphine and its prodrug sebacoly dinalbuphine ester in human plasma by ultra‐performance liquid chromatography–tandem mass spectrometry and its application to pharmacokinetic study in humans

Abstract: A rapid, simple, sensitive and selective ultraperformance liquid chromatography-tandem spectrometry (UPLC-MS/MS) method for the determination of nalbuphine and its prodrug sebacoly dinalbuphine ester (SDE) was developed and validated in human plasma. The sample pretreatment involves basification and iterative liquid-liquid extraction with ethyl-ether-dichloromethane (7:3, v/v) solution, followed by LC separation and positive electrospray ionization (ESI) API-3000 mass spectrometry detection. The chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
4
1
Order By: Relevance
“…Therefore, with a lower maximum blood concentration, DNS has a better safety profile than nalbuphine itself. No opioid antagonism or severe nalbuphine-induced AEs were observed in the DNS group, which may due to the single-dose extended release of DNS resulting in a relatively low maximum plasma concentration of nalbuphine ( C max = 16.8 ng/mL), 30 which led to the lower trend in dizziness, nausea, and vomiting observed in our study. While injection site reactions (ISRs) such erythema and swelling were commonly reported AEs in oil-based IM injection products.…”
Section: Discussioncontrasting
confidence: 46%
“…Therefore, with a lower maximum blood concentration, DNS has a better safety profile than nalbuphine itself. No opioid antagonism or severe nalbuphine-induced AEs were observed in the DNS group, which may due to the single-dose extended release of DNS resulting in a relatively low maximum plasma concentration of nalbuphine ( C max = 16.8 ng/mL), 30 which led to the lower trend in dizziness, nausea, and vomiting observed in our study. While injection site reactions (ISRs) such erythema and swelling were commonly reported AEs in oil-based IM injection products.…”
Section: Discussioncontrasting
confidence: 46%
“…Plasma concentrations of nalbuphine were determined by high‐performance liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), the details of which were reported in Huang's study 20 . Briefly, the plasma was mixed with nalbuphine‐d 3 (internal standard) and precipitated with acetonitrile (Fisher Technology Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is also reported that DNS was rapidly converted to nalbuphine in rats after intravenous administration exhibiting a mono‐exponential decay. A pilot clinical study demonstrated that when 75 mg of DNS was administered intramuscularly, nalbuphine was the only measurable product, while the plasma concentrations of DNS were below the low quantitation limit (Huang et al, ). There were two points worthy of concern, one was the issue of hydrolysis and the other was DNS lipophilicity.…”
Section: Introductionmentioning
confidence: 99%